2012
DOI: 10.1186/1471-2350-13-17
|View full text |Cite
|
Sign up to set email alerts
|

High resolution melting: improvements in the genetic diagnosis of hypertrophic cardiomyopathy in a Portuguese cohort

Abstract: BackgroundHypertrophic Cardiomyopathy (HCM) is a complex myocardial disorder with a recognized genetic heterogeneity. The elevated number of genes and mutations involved in HCM limits a gene-based diagnosis that should be considered of most importance for basic research and clinical medicine.MethodologyIn this report, we evaluated High Resolution Melting (HRM) robustness, regarding HCM genetic testing, by means of analyzing 28 HCM-associated genes, including the most frequent 4 HCM-associated sarcomere genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Five of these were synonymous mutations which had not been previously connected to pathogenicity, while 2 significant mutations, c.235C>T (rs3729712) and c.470C>T (CM031379) within exons 4 and 6 of TNNI3 , had been previously identified [10]. These mutations resulted in the mutated proteins p.R79C and p.A157V, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of these were synonymous mutations which had not been previously connected to pathogenicity, while 2 significant mutations, c.235C>T (rs3729712) and c.470C>T (CM031379) within exons 4 and 6 of TNNI3 , had been previously identified [10]. These mutations resulted in the mutated proteins p.R79C and p.A157V, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These mutations resulted in the mutated proteins p.R79C and p.A157V, respectively. These variants were not identified in 200 normal control samples [10]. Sanger sequencing revealed that the proband and her brother presented both double heterozygous mutations in TNNI3 whereas their father harbored the c.235C>T mutation in exon 4 and their mother the c.470C>T mutation in exon 6 (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent genetic studies have revealed that mutations in MYL2, encoding the human ventricular RLC, are more common than previously reported (for review, see Muthu et al 2012a;Szczesna 2003) and in just the last few years, new RLC mutations have been identified (Caleshu et al 2011;Santos et al 2012), with some detected multiple times and in different ethnic populations (Andersen et al 2009;Garcia-Pavia et al 2011). Multiple reports of MYL2 genetic variations have been published to date.…”
Section: Genetic Mutations In Myosin Regulatory Light Chain Lead To Cmentioning
confidence: 99%
“…Multiple reports of MYL2 genetic variations have been published to date. They are A13T (Andersen et al 2001;Hougs et al 2005;Poetter et al 1996), F18L (Flavigny et al 1998;Richard et al 2003), M20L (Olivotto et al 2008), E22K (Garcia-Pavia et al 2011;Kabaeva et al 2002;Poetter et al 1996); I44M (Santos et al 2012), N47K (Andersen et al 2001), G57E (Caleshu et al 2011, R58Q (Flavigny et al 1998;Kabaeva et al 2002;Morner et al 2003;Olivotto et al 2008;Richard et al 2003), P95A (Poetter et al 1996), K104E (Andersen et al 2001), E134A (Di Donna et al 2010;Olivotto et al 2008); D166V, IVS5-2 (an A > G transversion in intron 5 that leads to a premature termination codon) , and IVS6-1 (a G > C transversion in the acceptor splice site of intron 6) (Andersen et al 2001). Recently, a novel sarcomeric protein mutation in the MYL2 gene was identified by exome sequencing in a pedigree with familial dilated cardiomyopathy (DCM) .…”
Section: Genetic Mutations In Myosin Regulatory Light Chain Lead To Cmentioning
confidence: 99%
“…Recent genetic studies have revealed that mutations in the myosin RLC are more common than previously reported (for review see (Muthu et al 2012; Szczesna 2003)) and in just the past few years, new mutations in MYL2 have been identified (Alvarez-Acosta et al 2014; Olivotto et al 2008; Santos et al 2012), with some detected multiple times and in different ethnic populations (Andersen et al 2009; Garcia-Pavia et al 2011). In this review we focus on the effects of two HCM-causing mutations in the RLC, the N-terminal A13T mutation and the C-terminal K104E mutation (Figs.…”
Section: Mutations In Myl2mentioning
confidence: 99%